2002
DOI: 10.1136/bjsm.36.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Sea level and acute responses to hypoxia: do they predict physiological responses and acute mountain sickness at altitude?

Abstract: The results indicate that limited information can be gained on a subject's response to altitude by assessing physiological variables at sea level and a range of simulated altitudes before the subject carries out a trek at altitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…Our results are consistent with the data reported previously, which showed that the S O 2 value is a reliable predictor of which is susceptible to AMS [18][19][20][21][22][23][24][25][26][27]. Compared with other probable predictive indicators for AMS, such as HDV, HVR, BMI, and HR [9][10][11][12][13][14][15][16][17], S O 2 monitoring has the advantage of being easily operated, noninvasive, and reliable. Because the susceptibility to AMS is variable in individuals, the reason for mixed results of different specific studies maybe due to influence of the different exposure time, ascent velocity, and factors that affect oxygenation of the erythrocyte and associated S O 2 measurements.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our results are consistent with the data reported previously, which showed that the S O 2 value is a reliable predictor of which is susceptible to AMS [18][19][20][21][22][23][24][25][26][27]. Compared with other probable predictive indicators for AMS, such as HDV, HVR, BMI, and HR [9][10][11][12][13][14][15][16][17], S O 2 monitoring has the advantage of being easily operated, noninvasive, and reliable. Because the susceptibility to AMS is variable in individuals, the reason for mixed results of different specific studies maybe due to influence of the different exposure time, ascent velocity, and factors that affect oxygenation of the erythrocyte and associated S O 2 measurements.…”
Section: Discussionsupporting
confidence: 95%
“…There are several predictive methods for AMS susceptibility, which have been supported by the previous research, but none is easily measured [9][10][11]. There is not a consistent association between heart rate (HR) [12,13] or blood pressure 12 and AMS.…”
Section: Introductionmentioning
confidence: 94%
“…[3,14,25]. Thus, assessment of AMS susceptibility due to repeated altitude exposures may provide a more adequate basis for prediction than occasional observations as done in various studies [6,10,12,18]. Richalet et al [9] and Rathat et al [8], for instance, demonstrated that 80%, and we showed that 86%, of AMS susceptible subjects could be predicted when assessing AMS susceptibility on repeated observations [5; Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, Hayat et al [16] investigated the SaO 2 increase after voluntary hyperventilation at altitude and found a significant correlation to the AMS score, and also, the gag reflex has been shown to be related to AMS during a trek to high altitude [17]. Whereas Bärtsch et al [4] found lower SaO 2 values at the first days at 4,559 m in subjects with AMS, Grant et al [18] compared SaO 2 values at different simulated altitudes and reported no relation to the AMS score at these altitudes during a subsequent trek. In a recent investigation, Savourey et al [19] compared normo-and hypobaric exercise tests to determine the susceptibility to AMS.…”
Section: Resultsmentioning
confidence: 96%
“…On the endothelial point of view, the definition of hypoxia could be the level of oxygen at which the clonogenic PB-EPCs response starts. Furthermore, this cellular response might be used for studies aimed to predict the adverse effects of high altitude since it has been shown that limited informations can be obtained by assessing only cardiorespiratory physiological variables at sea level and at a range of simulated altitudes [37]. …”
Section: Discussionmentioning
confidence: 99%